Acaciella angustissima (Mill.) Brit. & Rose: Botanical Features, Distribution, Medicinal and Pharmacological Properties - Collen Musara,; Elizabeth Bosede Aladejana, (Journal of Pharmacy and Nutrition Sciences, 2020)
Acaciella angustissima (Mill.) Brit. & Rose is a multipurpose deciduous thornless shrub or small tree that belongs to the family Fabaceae and subfamily Mimosoideae. This study aimed to explore A. angustissima, a leguminous shrub with medicinal, ecological and industrial potential. A mixed-method approach, which included consolidating quantitative and qualitative research, was utilized to put together the review with the main focus being on sub-Saharan Africa. However, case studies and literature from South Africa were also utilized. A. angustissima is a good source of phenolic compounds. It is used to relieve painful toothache, rheumatism, skin lesions, bloody diarrhea and mucoid diarrhea. It also displays a mild antimicrobial effect and has the ability to inhibit growth in malignant tumors. The study acknowledged Acaciella angustissima as an important agroforestry tree species that improve the quality of life of resource-poor farmers, reducing poverty and promoting sustainability of the natural resources base and economic growth